2018
DOI: 10.1007/164_2017_90
|View full text |Cite|
|
Sign up to set email alerts
|

Chronic Alcohol, Intrinsic Excitability, and Potassium Channels: Neuroadaptations and Drinking Behavior

Abstract: Neural mechanisms underlying alcohol use disorder remain elusive, and this lack of understanding has slowed the development of efficacious treatment strategies for reducing relapse rates and prolonging abstinence. While synaptic adaptations produced by chronic alcohol exposure have been extensively characterized in a variety of brain regions, changes in intrinsic excitability of critical projection neurons are understudied. Accumulating evidence suggests that prolonged alcohol drinking and alcohol dependence p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 162 publications
3
32
1
Order By: Relevance
“…The mPFC, including the prelimbic (PL) and infralimbic (IL) subregions, receives glutamatergic inputs from the BLA that can promote anxiety-like behaviors (Felix-Ortiz et al, 2016) and are modulated by chronic stress (Lowery-Gionta et al, 2018;Marcus et al, 2019). Acute withdrawal from alcohol exposure has been found to disrupt synaptic transmission and intrinsic excitability of pyramidal neurons of the mPFC at different stages of alcohol dependence; particularly, the dependence-inducing chronic intermittent ethanol (CIE) model enhances excitatory drive and intrinsic excitability in pyramidal neurons (Cannady et al, 2018; , whereas the drinking-in-the-dark (DID) model of pre-dependence binge-like drinking impaired excitatory transmission . Our FST-induced cFos expression data revealed that forced abstinence from alcohol dampened neuronal activation in the female PFC (Figure 3B).…”
Section: Discussionmentioning
confidence: 99%
“…The mPFC, including the prelimbic (PL) and infralimbic (IL) subregions, receives glutamatergic inputs from the BLA that can promote anxiety-like behaviors (Felix-Ortiz et al, 2016) and are modulated by chronic stress (Lowery-Gionta et al, 2018;Marcus et al, 2019). Acute withdrawal from alcohol exposure has been found to disrupt synaptic transmission and intrinsic excitability of pyramidal neurons of the mPFC at different stages of alcohol dependence; particularly, the dependence-inducing chronic intermittent ethanol (CIE) model enhances excitatory drive and intrinsic excitability in pyramidal neurons (Cannady et al, 2018; , whereas the drinking-in-the-dark (DID) model of pre-dependence binge-like drinking impaired excitatory transmission . Our FST-induced cFos expression data revealed that forced abstinence from alcohol dampened neuronal activation in the female PFC (Figure 3B).…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we identified a DMR that maps to an ion channel gene previously implicated in excessive drinking, ethanol-seeking behaviors, and ethanol-induced plasticity of intrinsic excitability (6,10,11,13,17). Our analysis identified a DMR that spans exon 1 and part of intron 1 of monkey and mouse KCNN3 in a region containing CpGs that are highly conserved across species.…”
Section: Discussionmentioning
confidence: 82%
“…While the technicians were not blind to the treatment condition (ethanol or control), the intake data were collected and recorded in an automated fashion by computer and analyzed by individuals who did not interact with or know the drinking status of the monkeys. All of the animal 6 procedures used in this study were approved by the ONPRC IACUC and were performed in accordance with the NIH and the National Resource Council's Guide for the Care and Use of Laboratory Animals.…”
Section: Ethanol Self-administration In Rhesus Macaquesmentioning
confidence: 99%
See 2 more Smart Citations